Regenerasi Dakwah Humanis di Era Cyber Religion - Masluhah Masluhah; Ahmad Hafid (Alhadharah: Jurnal Ilmu Dakwah, 2021)
Da'wah is the most important part of religion. All forms of teaching and faith dissemination to the worship procedures are driven by da'wah activities. As a dynamic activity, da'wah continues to experience changes in methods and strategies that are considered effective and in line with the changing times. In the digitalization, most of religious activities have shifted to virtual spaces which are considered flexible, efficient, and more effective. Cyber religion is present as an answer to the digitalization demands in the religious sector. In addition to all its benefits, cyber religion also has a negative impact by increasing the prevalence of hate speech in the name of religion expressed by the laity to the preachers. So a special formulation is needed to stem the increasing number of religion hate speech in the virtual space. The Prophet Muhammad as a role model for the people of all time has taught and exemplified our tips for humanist da'wah so that not only transmits religious teachings, but also creating unity of the ummah. These efforts can be realized in three ways; Muhammad training center, determines the preache qualifications and ethics, conducts mentoring and evaluation.